ANALISIS PENGARUH TATO, WCTO, DAN DER TERHADAP NILAI PERUSAHAAN DENGAN ROA SEBAGAI VARIABEL INTERVENING (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2009-2013) - Rahmawati Budi Utami; Prasetiono Prasetiono (JURNAL STUDI MANAJEMEN ORGANISASI, 2016)
The aims of this research is to examine the direct effect and indirect effect of Total AssetTurnover, Working Capital Turnover, Debt to Equity Ratio on Firm Value with ReturnOn Asset as an intervening variable.This research sample is manufacturing companies listed in the Indonesia Stock Exchange(IDX) period 2009-2013 by using purposive sampling method. There are 64manufacturing companies selected as sample. The method of analysis used is PathAnalysis, the development of multiple linear regression.Using multiple regression analysis, it is known that TATO has positive significant effecton ROA. WCTO and DER has negative significant effect on ROA. TATO has positive notsignificant effect on Firm Value. WCTO has negative significant effect on Firm Value.DER and ROA has positive significant effect on Firm Value. The result of path analysisshowed that TATO influence Firm Value through ROA. Besides, it was found that thevalue of the adjusted R square for the equation ROA is 25,3% while the value of theadjusted R square for the equation PBV is 39,7%.Keywords: Total Asset Turnover (TATO), Working Capital Turnover (WCTO), Debt toEquity Ratio (DER), Return On Asset (ROA), Firm Value